Solve for m y=md+b

Math
y=md+b
Rewrite the equation as md+b=y.
md+b=y
Subtract b from both sides of the equation.
md=y-b
Divide each term by d and simplify.
Tap for more steps…
Divide each term in md=y-b by d.
mdd=yd+-bd
Cancel the common factor of d.
Tap for more steps…
Cancel the common factor.
mdd=yd+-bd
Divide m by 1.
m=yd+-bd
m=yd+-bd
Move the negative in front of the fraction.
m=yd-bd
m=yd-bd
Solve for m y=md+b

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top